Influência da posição e tempo de irradiação sobre a capacidade de desinfecção em forno de micro-ondas - Mascarenhas Oliveira, Ana Carolina; Antunes Pereira Pinelli, Lígia [UNESP]; Barbosa Tavares da Silva, Regina Helena [UNESP] (Sociedade Portuguesa de Estomatologia e Medicina Dentaria (SPEMD), 2012)
Objective: To evaluate the variations of temperature in 2 models of domestic micro-wave ovens, single emission (F 1) and dual emission of waves (F 2), to investigate areas of higher and lower intensity of the electromagnetic field. Materials and methods: A beaker containing water (60mL, 26°C) was irradiated into each of 5 positions (front - P 1; right - P 2; posterior - P 3; left - P 4; central - P 5) within each oven (900W/ 2min). To evaluate the effectiveness of disinfection in F 2, Bacillus subtilis suspension was irradiated in each of the 5 positions for 2, 4 and 6minutes. Data were analyzed by Kruskal-Wallis and nonparametric multiple comparisons at 5% significance level. Results: 84.80°C (F 1) and 92.01°C (F 2) were mean levels of temperature. For F 1, the positions P 1, P 2, P 3 and P 5 showed similar values among them and upper than P 4, while for F 2, the positions P 1, P 2 and P 4 were similar among them and upper than P 3 and P 5. Kruskal-Wallis test found significant differences between positions and models of ovens (p<0.05). It was observed that P 2 promoted bacterial death from 4min of irradiation, while the other positions promoted disinfection at 6min of irradiation. Conclusion: The protocols of position and time specified for the various procedures in microwave ovens can be different according to the characteristics of each device due to the electromagnetic field heterogeneity. © 2011 Sociedade Portuguesa de Estomatologia e Medicina Dentária.
Influence of the position and irradiation time on the ability of disinfection in microwave oven
Keywords: Bacillus subtilis; Disinfection; Microwaves; disinfection; electromagnetic field; irradiation; microwave oven; priority journal; temperature